The Use of Monopoly Media to Improve Primary Student’s Critical Thinking Skills in Science Learning (Universitas Negeri Semarang, 2019)
The purpose of this research was to investigate the difference improvement of critical thinking skills by using inquiry model assisted with monopoly media with direct instruction learning model in Primry Schools. The method used in this research was a type of quantitative research methods especially Non equivalent of pre-test and post-test control group design was used with 77 students as the research subjects of Diponegoro distric at Sempor Kebumen. The data collection techniques used were test, interviews, observation. The results of the present research showed that the critical thinking skills of students by using inquiry model assisted with monopoly media is better than those taught by direct instruction learning model and the result of the t-test obtained significance value of 0.003 < 0.05. The percentage of critical value of subject matter of Science Learning based on students worksheets (LKS) and experiments for high critical criteria are 13.88%, critical criteria 66.67%, moderate critical criteria 19.44%. Then, the average final scores of students in the experimental class was 80.52% and the control class was 74.63%, While the stage of average critical thinking was at the level 4 which is to formulate arguments and determine the outcome of the consideration by the integration between initial concept and experiment. Therefore, it can be concluded that the use of inquiry model assisted with monopoly media is more effective used than that of direct instruction learning model.